Immunosuppressive effect of zhankuic acid C from Taiwanofungus camphoratus on dendritic cell activation and the contact hypersensitivity response. Issue 20 (15th October 2015) - Lin, Ming-Kuem; Lee, Meng-Shiou; Chang, Wen-Te; Chen, Hsing-Yu; Chen, Jin-Fu; Li, Yi-Rong; Lin, Chi-Chen; Wu, Tian-Shung
Graphical abstract: Abstract: Some ergostane triterpenoids from Taiwanofungus camphoratus have been shown to exhibit anti-inflammatory activity in vitro. However, the effect of ergostane triterpenoids on the immune response remains unknown. In this study, we elucidated that ergostane triterpenoids significantly decreased the cytokines and chemokine release by dendritic cells (DC) and that, in the case of zhankuic acid C (ZAC), the decrease was dose-dependent and inhibited DC maturation. ZAC inhibited the contact hypersensitivity response and infiltrative T cells in the ears of DNFB-stimulated mice. Thus, we demonstrate for the first time that ZAC exhibits an immunosuppressive effect on DC activation and the contact hypersensitivity response. It is suggested that ZAC can potentially be used for treating chronic inflammation and autoimmune diseases.